Bank’s Legal Liability toward Customers in Cases of Transaction Restrictions under LPS Special Surveillance - Diana R.W. Napitupulu (Universitas Muhammadiyah Surabaya, 2026)
This article analyzes the legal liability of banks toward customers arising from transaction restrictions imposed during the Indonesia Deposit Insurance Corporation’s (LPS) Special Surveillance period. The study aims to determine whether such regulatory restrictions limit or extinguish banks’ contractual, statutory, and tort-based obligations to customers. This research employs normative legal research with statutory and conceptual approaches. The findings demonstrate that compliance with mandatory regulatory directives does not automatically absolve banks from legal liability. While transaction restrictions may justify temporary non-performance of contractual obligations, they cannot be categorically classified as force majeure, because the restrictions arise from regulatory intervention linked to the bank’s financial condition rather than from unforeseeable external events beyond the parties’ control. Banks therefore remain liable where restrictions are inadequately disclosed, applied arbitrarily, or attributable to prior mismanagement that precipitated the bank’s financial deterioration. The study further finds that regulatory intervention does not result in a full transfer of liability from banks to the state or LPS, as LPS’s mandate as a public legal entity is confined to supervisory and resolution functions rather than assuming private law responsibilities toward customers. Consequently, customers retain access to legal remedies through civil claims, administrative complaints, and judicial review of regulatory actions. This article concludes that clearer statutory allocation of liability, enforceable disclosure standards, and transparent procedures during Special Surveillance are essential to ensuring legal certainty and balancing financial system stability with effective customer protection.